Utility of Papanicolaou’s smears in the diagnosis of premalignant and malignant lesions of the cervix in a tertiary care centre of South Gujarat, India - Gandhi, Shivangi S.; Shah, Pinal C. (International Journal of Research in Medical Sciences, 2019)
Background: "Preventable but not prevented", this is the reality of cervical cancer today, at least in developing countries. 80% of all the cases of cervical cancer occur in these developing countries. In India, cervical cancer is the leading cause of cancer related deaths in women. The Papanicolaou test is simple, quick, and painless. It is capable of detecting cervical cancer at an early stage and is used widely in developed countries, where it has decreased both the incidence and mortality of cervical cancer. Objective of the study was conducted to determine the importance of conventional Pap smears for the diagnosis of inflammatory, premalignant and malignant lesions of the cervix. Methods: This cross-sectional study was conducted from January 2017 to June 2018 on 2000 women coming for a Pap smear examination in Government Medical College attached to New Civil Hospital, Surat. After doing Pap stain, all cases were reported as per the 2014 Bethesda system. Results: A total of 2000 cases of Pap smears were received out of which 1914(95.7%) cases were satisfactory for evaluation, 86(4.3%) cases were unsatisfactory. The frequency of epithelial abnormalities was 3.66%. The age group of 51-60 years showed the highest epithelial abnormalities. The frequency of epithelial abnormalities in asymptomatic women was 2.3%. Out of the 1844 cases, 103(5.6%) showed changes of atrophy, 1011(54.8%) cases showed inflammatory/reactive changes, whereas organisms were seen in 558(30.3%) cases. Conclusions: Pap smear happens to be an economical, safe and pragmatic diagnostic tool for early detection of cervical cancer.